Association Between Neutrophil-to-Lymphocyte Ratio and Vitamin D Deficiency in Patients With Sickle Cell Disease: A Cross-Sectional Study in Central Uganda - Enoch Muwanguzi; Jazira Tumusiime; Geofrey Salamu; Charles Nkubi Bagenda; Benson Okongo (Cureus, 2026)
Background: Vitamin D deficiency and chronic inflammation are prevalent in individuals with sickle cell disease (SCD), contributing to disease severity. Hematological ratios are simple inflammatory markers that can have various clinical outcomes. The main aim of our study was to assess the association between hematological ratios and vitamin D deficiency among patients with SCD in Central Uganda. Methods: We conducted a cross-sectional study among patients with SCD attending Mengo Hospital, Central Uganda. Data were collected using a researcher-administered questionnaire supplemented with information from participants’ medical records. Anthropometric measurements were taken, and a blood sample was drawn for laboratory measurement of hematological parameters and serum vitamin D levels. Results: Out of the 213 participants, 101 (47.4%) had serum 25-hydroxyvitamin D (25(OH)D) concentrations <20 ng/mL, indicating vitamin D deficiency, while 68 (31.9 %) had levels between 20-30 ng/mL, consistent with vitamin D insufficiency. Participants with vitamin D deficiency had a higher neutrophil-to-lymphocyte ratio (NLR) (0.27, IQR: 0.13-0.88) compared to those without vitamin D deficiency (0.22, IQR: 0.10-0.63), although the difference was not statistically significant (p=0.45). However, after adjusting for potential confounders, both the second (adjusted prevalence ratio (aPR)=1.83; 95% CI: 1.25-2.68; p=0.002) and third tertiles (aPR=1.74; 95% CI: 1.04-2.91; p=0.033) of the neutrophil-to-lymphocyte ratio were significantly associated with increased prevalence of vitamin D deficiency. Conclusions: Vitamin D deficiency is prevalent among patients with SCD in Central Uganda. High NLR is potentially associated with vitamin D deficiency among patients with SCD.
Keywords: central uganda; deficiency; hematological ratios; insufficiency; vitamin d